EKSPLORASI MAKNA KONOTATIF LEKSIKON DALAM LIRIK LAGU ALBUM FIGURA RENATA (SELF TITLED) DAN ALBUM HARA KARYA GRUP BAND FIGURA RENATA - Lusi Yolanda; Ngusman (Saka Bahasa: Jurnal Sastra, Bahasa, Pendidikan, dan Budaya, 2026)
This research is motivated by the large number of connotative nouns used in song lyrics. This research aims to describe the form of positive connotation, the form of negative connotation, and the comparative frequency of the use of noun connotation in the lyrics of the album Figura Renata (Self Titled) and the album Hara by the band Figura Renata. This type of research is qualitative research with descriptive methods. The research data are in the form of connotative nouns in the song lyrics obtained through techniques and words. The data sources of this research are two albums Figura Renata (self title) and the album Hara by the band Figura Renata. This research data is explained based on semantic theory, especially the theory of connotative meaning. The results of the study found 122 connotative noun data consisting of 85 positive connotation data (69.67%) and 37 negative connotation data (30.33%). In positive connotation, the use of visual imagery is the most dominant, namely 70 data (82.35%), while in negative connotation the sense of sight is also dominant as much as 23 data (62.16%). The form or form of positive connotation was found as many as 41 data while the form or form of negative connotation was as many as 27 data. The results of the study show that the use of positive connotation is more dominant than negative connotation, and the lyrics of the song Figura Renata tend to build meaning through visual imagery and positive feeling values. This finding shows that the use of connotative nouns in the lyrics of the song Figura Renata not only functions as an aesthetic element, but also builds depth of meaning and reflective messages. Penelitian ini dilatarbelakangi oleh banyaknya penggunaan nomina berkonotasi dalam lirik lagu. Penelitian ini bertujuan untuk mendeskripsikan wujud konotasi positif, wujud konotasi negatif, dan frekuensi perbandingan penggunaan konotasi nomina dalam lirik lagu album Figura Renata (Self Titled) dan album Hara karya grup band Figura Renata. Jenis penelitian ini adalah penelitian kualitatif dengan metode deskriptif. Data penelitian berupa kata-kata nomina berkonotasi dalam lirik lagu yang diperoleh melalui teknik simak dan catat. Sumber data penelitian ini adalah dua album Figura Renata (self titled) dan album Hara karya grup band Figura Renata. Data penelitian ini dianalisis berdasarkan teori semantik khususnya teori makna konotatif. Hasil penelitian ditemukan 122 data nomina berkonotasi yang terdiri atas 85 data konotasi positif (69,67%) dan 37 data konotasi negatif (30,33%). Pada konotasi positif, penggunaan citraan indra penglihatan paling dominan, yaitu 70 data (82,35%), sedangkan pada konotasi negatif indra penglihatan juga dominan sebanyak 23 data (62,16%). Bentuk atau wujud konotasi positif ditemukan sebanyak 41 data sedangkan bentuk atau wujud konotasi negatifnya sebanyak 27 data. Hasil penelitian menunjukkan bahwa penggunaan konotasi positif lebih dominan dibandingkan konotasi negatif, serta lirik lagu Figura Renata cenderung membangun makna melalui citraan visual dan nilai rasa positif. Temuan ini menunjukkan bahwa penggunaan nomina berkonotasi dalam lirik lagu Figura Renata tidak hanya berfungsi sebagai unsur estetis, tetapi juga membangun kedalaman makna dan pesan reflektif.